EFFECTIVENESS OF THE IMPLEMENTATION OF MERIT SYSTEM IN FILLING STRUCTURAL POSITIONS IN THE HUMAN RESOURCES DEVELOPMENT AGENCY OF SINJAI REGENCY SOUTH SULAWESI PROVINCE - Ambarawati, Gusti Ayu; Gustiana, Nurlita Putri; Dewi, Ayu Raditya Kencana (Institut Pemerintahan Dalam Negeri, 2024)
This study aims to determine and describe the effectiveness of the implementation of the merit system in filling structural positions in Sinjai Regency, South Sulawesi Province. This study used a descriptive qualitative method with an inductive approach. The data collection techniques covered observation, interviews and documentation. Data were analyzed using some stages, namely data reduction, data exposure, and drawing conclusions. The effectiveness of the implementation of the merit system in filling structural positions in the Human Resources Development Agency (BKPSDMA) of Sinjai Regency was based on Duncan's theory of effectiveness measures covering goal setting, integration and adaptation. The results of the study showed that the merit system in filling structural positions in the Human Resources Development Agency (BKPSDMA) of Sinjai Regency has been well implemented. This is indicated by the leadership’s commitment to the implementation of the merit system in filling structural positions, a strong legal basis, and support from the South Sulawesi provincial government for the BKPSDMA. However, the implementation faced some challenges, namely budget constraints, employee interest in taking competency tests, the unavailability of an Assessment Center, and the absence of functional assessors. The effort to address those challenges includes providing Assessment Center facilities, allocating budgets for the implementation of the merit system, and providing motivation and encouragement to employees.